2012
DOI: 10.1134/s0006297912020125
|View full text |Cite
|
Sign up to set email alerts
|

Ah-receptor-independent stimulation of hepatoma 27 culture cell proliferation by polycyclic aromatic hydrocarbons

Abstract: The proliferative effect of some compounds that are aryl hydrocarbon (Ah) receptor ligands was studied on hepatoma 27 cells with absent expression of Ah receptor. Compounds of the polycyclic aromatic hydrocarbon (PAH) class benzo/a/pyrene, 3-methylcholanthrene, 7,12-dimethylbenz/a/anthracene, and benzo/e/pyrene as well as β-naphthoflavone (β-NF) and chlorinated hydrocarbon Aroclor 1254 were studied. It was found that carcinogenic PAH and β-NF stimulate cell proliferation both under conditions of standard serum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 43 publications
0
2
0
Order By: Relevance
“…The Ah-receptor-mediated effects are fairly broad and include detoxification, cell proliferation, and migration [127]. However, benz[a]pyrene was shown to activate cell proliferation [124] via an Ah-receptor-independent pathway [128]. In addition to the activation of the proliferation of gill epithelial cells by soot components, this process can also be induced by apoptosis (the so-called apoptosis-induced compensatory proliferation) [129].…”
Section: Paradoxical Effect Of Soot Microparticles On Cell Proliferat...mentioning
confidence: 99%
“…The Ah-receptor-mediated effects are fairly broad and include detoxification, cell proliferation, and migration [127]. However, benz[a]pyrene was shown to activate cell proliferation [124] via an Ah-receptor-independent pathway [128]. In addition to the activation of the proliferation of gill epithelial cells by soot components, this process can also be induced by apoptosis (the so-called apoptosis-induced compensatory proliferation) [129].…”
Section: Paradoxical Effect Of Soot Microparticles On Cell Proliferat...mentioning
confidence: 99%
“…The synthetic polyaromatic hydrocarbon, β-naphthoflavone (β-NF), has been extensively used to analyze the effect of xenobiotics on a large number of genes involved in metabolic and adaptive processes (20,21). In previous studies, we showed that both in vitro and in vivo expression of Dp71 in hepatic cells is repressed by β-NF (22).…”
Section: The Polyaromatic Hydrocarbon β-Naphthoflavone Alters Bindingmentioning
confidence: 99%
“…These compounds are classical substrates and inducers of cytochrome P450 enzymes (CYP), particularly the isoforms CYP1B1 and CYP1A1 [15], which in turn generate highly reactive metabolites, which react with proteins and DNA, leading to mutagenesis and carcinogenesis [16]. In addition to these effects, they are estrogenic compounds, modulators of cell cycle, proliferation and even modulators of angiogenesis [17][18][19][20].…”
Section: Biomedical Research 2018; 29 (12): 2663-2671mentioning
confidence: 99%